2021
DOI: 10.3390/ma14081913
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Abaqus Implementation of the Phase Field Fracture Method Using Only a User Material Subroutine

Abstract: We present a simple and robust implementation of the phase field fracture method in Abaqus. Unlike previous works, only a user material (UMAT) subroutine is used. This is achieved by exploiting the analogy between the phase field balance equation and heat transfer, which avoids the need for a user element mesh and enables taking advantage of Abaqus’ in-built features. A unified theoretical framework and its implementation are presented, suitable for any arbitrary choice of crack density function and fracture d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 49 publications
(86 reference statements)
1
48
0
Order By: Relevance
“…the centre of the pin. Furthermore, [23] opted for l = 0.1 [mm], in this manuscript as well as in [48], l = 0.25 [mm]. Finally, from Figure 8b, it observed that the final phase-field fracture topology does match the experimentally observed fracture patterns in Figure 7.…”
Section: Brittle: Notched Concrete Specimen With a Holesupporting
confidence: 61%
See 1 more Smart Citation
“…the centre of the pin. Furthermore, [23] opted for l = 0.1 [mm], in this manuscript as well as in [48], l = 0.25 [mm]. Finally, from Figure 8b, it observed that the final phase-field fracture topology does match the experimentally observed fracture patterns in Figure 7.…”
Section: Brittle: Notched Concrete Specimen With a Holesupporting
confidence: 61%
“…Figure 8a presents the load-displacement curves obtained using the Lagrange Multiplier Method and the Penalty method, along with those from the literature [23,48]. The curves corresponding to the Lagrange Multiplier Method and the Penalty method coincide, and predict peak loads close to those obtained in [23] and [48]. However, the load-displacement curves are significantly different from [23].…”
Section: Brittle: Notched Concrete Specimen With a Holementioning
confidence: 69%
“…As described in Appendix C, we take advantage of the analogy between the phase field evolution law and the heat transfer equation to implement the model into the finite element package ABAQUS using solely a user-material subroutine (UMAT) (see Refs. [36,37]). Maurini [33], where a Drucker-Prager failure surface was also adopted.…”
Section: Particularisation To the Drucker-prager Failure Surfacementioning
confidence: 99%
“…Recently, Navidtehrani et al [52] proposed a clever technique to use Abaqus's coupled thermal-stress analysis module to solve the phase-field fracture problem in a single UMAT code. There are promising solutions [67,53] in the literature to replace the quadratic phase-field representation with a linear function and an energy threshold. However, a thermodynamically consistent scheme has yet to be proposed in the finite element code Abaqus (see the discussion on existing models).…”
Section: Introductionmentioning
confidence: 99%